2016
DOI: 10.1002/2016jc011922
|View full text |Cite
|
Sign up to set email alerts
|

Observations and modeling of a tidal inlet dye tracer plume

Abstract: A 9 km long tracer plume was created by continuously releasing Rhodamine WT dye for 2.2 h during ebb tide within the southern edge of the main tidal channel at New River Inlet, NC on 7 May 2012, with highly obliquely incident waves and alongshore winds. Over 6 h from release, COAWST (coupled ROMS and SWAN, including wave, wind, and tidal forcing) modeled dye compares well with (aerial hyperspectral and in situ) observed dye concentration. Dye first was transported rapidly seaward along the main channel and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 64 publications
2
41
0
Order By: Relevance
“…The potential to map dispersion patterns via remote sensing was first demonstrated in coastal environments [6,7]. Clark et al [6] showed that passive optical image data could be used to estimate Rhodamine WT dye concentrations in the surf zone and identify eddies and other small-scale structures (on the order of 10 m) associated with the dispersion of a dye pulse.…”
Section: Introductionmentioning
confidence: 99%
“…The potential to map dispersion patterns via remote sensing was first demonstrated in coastal environments [6,7]. Clark et al [6] showed that passive optical image data could be used to estimate Rhodamine WT dye concentrations in the surf zone and identify eddies and other small-scale structures (on the order of 10 m) associated with the dispersion of a dye pulse.…”
Section: Introductionmentioning
confidence: 99%
“…COAWST consists of a mesoscale atmosphere model, a regional ocean model, a model for simulating surface waves, a sediment transport model, and a dynamic coupler to exchange data fields between the submodels. It has been used in a number of studies on sediment dynamics in coastal oceans, during both storm and nonstorm conditions (e.g., Feddersen et al, ; Kumar et al, ; Kumar & Feddersen, ; Olabarrieta et al, ; Sclavo et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…COAWST consists of a mesoscale atmosphere model, a regional ocean model, a model for simulating surface waves, a sediment transport model, and a dynamic coupler to exchange data fields between the submodels. It has been used in a number of studies on sediment dynamics in coastal oceans, during both storm and nonstorm conditions (e.g., Feddersen et al, 2016;Kumar et al, 2015;Kumar & Feddersen, 2016;Olabarrieta et al, 2011;Sclavo et al, 2013). In our implementation of COAWST for Chesapeake Bay, we did not run the Weather and Research Forecasting model for the regional atmosphere and couple it to the ocean and wave models since wind speeds over fetch-limited Chesapeake Bay are challenging to predict.…”
Section: Methodsmentioning
confidence: 99%
“…Here we report on marine X‐band radar observations of the New River Inlet, North Carolina, utilized to observe morphological variability. The fieldwork was conducted during the Office of Naval Research (ONR) sponsored Inlets and Rivers Mouth Dynamics Departmental Research Initiative (RIVET‐I) experiment in May 2012 (e.g., Chen et al, ; Feddersen et al, ; MacMahan et al, ; Pianca et al, ; Rogowski et al, ; Spydell et al, ; Wargula et al, ; Zippel & Thomson, ). The work uses ensemble averages of continuous X‐band radar scans (42 rotations per minute) to delineate shoal positions within inlet.…”
Section: Introductionmentioning
confidence: 99%